1993
DOI: 10.1159/000243939
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Development of Brunner’s Glands in the Rat: Morphometrical Study

Abstract: Perinatal changes of the Brunner’s glands in rats from fetal day 20 through neonatal day 3 were studied morphometrically and electron-microscopically. Percentage volume of secretory granules of the gland cells did not change from fetal day 20 through neonatal day 1 and increased significantly from neonatal days 1-2; this level was maintained through neonatal day 3. Electron-microscopically, the gland cells during the fetal days were rich in free ribosomes. The Golgi apparatus and rough-surfaced endoplasmic ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…BG secretions are alkaline and fluid, and respond to parasympathetic vagal stimuli (Moore et al, 2000). Their alkalinity helps neutralize the chymo acid that originates in the stomach, and also provides optimal conditions for enzyme action on pancreatic juices (Morikawa et al;Olsen et al, 1994). Some studies have demonstrated that somatostatin is able to inhibit BG secretions (Kirkegaard et al, 1984;Olsen et al).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BG secretions are alkaline and fluid, and respond to parasympathetic vagal stimuli (Moore et al, 2000). Their alkalinity helps neutralize the chymo acid that originates in the stomach, and also provides optimal conditions for enzyme action on pancreatic juices (Morikawa et al;Olsen et al, 1994). Some studies have demonstrated that somatostatin is able to inhibit BG secretions (Kirkegaard et al, 1984;Olsen et al).…”
Section: Discussionmentioning
confidence: 99%
“…Its excretory ducts penetrate the muscle mucosa and reach the base of the intestinal crypts, where they eliminate their secretion (even though they are able to eliminate their secretion through their own ducts, which reach the duodenal surface by going through its mucosa) (Morikawa et al, 1993). From this point, the secretion is discharged into the duodenal lumen.…”
Section: Discussionmentioning
confidence: 99%